Wave energy converters design combining hydrodynamic performance and structural assessment - Gianmaria Giannini (2022)
The design of a wave energy converter (WEC) is a many-sided and important assignment that determines its future technical and economic viability. Presently, there is a lack of structured design methodologies that take into account both the hydrodynamic performance, structural reliability and economic data from early development stages. Therefore, a new methodology is proposed, aiming for a viable predesign solution for avoiding major setbacks at later stages. It includes a series of steps related to the initial design definition, hydrodynamic analysis, yield strength investigation and early-stage economic assessment. For demonstration, the methodology is applied to progress a sloped motion WEC for near-shore locations. The original WEC configuration is also assessed and the novel design, which allows reducing the mass of floating elements by 70%, is developed. It is found that: for recurrent sea states, the capture width ratio of the new design (20-40%) is similar to the one of the original design (20-50%), the estimated cost of the device is reduced by 28.6% and the payback period is reduced by 2.4 years. Overall, the results obtained for the case study demonstrated the interest in the proposed methodology that can assist in the development and analysis of early-stage WEC concepts. (c) 2022 Elsevier Ltd